2020
DOI: 10.1002/adfm.202005303
|View full text |Cite
|
Sign up to set email alerts
|

InP/ZnS/ZnS Core/Shell Blue Quantum Dots for Efficient Light‐Emitting Diodes

Abstract: As the concerns about using cadmium-based quantum dots (QDs) in display are growing worldwide, InP QDs have drawn much attention in quantum dot light-emitting diodes (QLEDs). However, pure blue InP based QLED has been rarely reported. In this work, first of all, pure blue InP/ZnS QDs with emission wavelength of 468 nm and quantum yield of 45% are synthesized. Furthermore, zinc oleate and STOP are used as precursors to epitaxially grow the second ZnS shell. The residual zinc stearate reacted with STOP to form Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
113
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(113 citation statements)
references
References 30 publications
0
113
0
Order By: Relevance
“…The relative position of the energy levels of the two semiconductors is still poorly understood in spite of their extensive studies [ 31 ]. The approximate location of some of those energy levels is given in [ 34 ]. One can assume that ZnS has the ground state energy 7.0 eV.…”
Section: Discussionmentioning
confidence: 99%
“…The relative position of the energy levels of the two semiconductors is still poorly understood in spite of their extensive studies [ 31 ]. The approximate location of some of those energy levels is given in [ 34 ]. One can assume that ZnS has the ground state energy 7.0 eV.…”
Section: Discussionmentioning
confidence: 99%
“…These two drawbacks may be addressed through a controlled synthesis of InP/ZnSe/ZnS core/shell system. 19,20 Stoichiometric control within both the core and shell regions achieved by purification of the precursors between the different shell growth stages, was found to result in InP/ZnSe/ZnS nanocrystals with a high quantum yield of 93% and QD-LED external quantum efficiency (EQE) of 12.2% (Figure 5b). 20 A follow-up study then demonstrated the achievement of highly spherical and symmetrical core/shell structure nanocrystals that further increased the stability and efficiency of the system.…”
Section: Rohs Compatible Colloidal Quantum Materialsmentioning
confidence: 99%
“…Micro-LEDs have the advantages of high contrast, low power consumption, long life, and fast response time, but they can be improved further [ 35 ]. Zhang et al proposed the use of pure blue double-shell InP/(ZnS) QDs with an emission wavelength of 468 nm and a quantum yield of 45%, and they managed to increase EQE by 2.8 times [ 36 ]. Yang Li et al proposed the application of microfluidic technology combined with a red–green perovskite QDs color conversion layer for use in micro-LEDs displays and achieved a wide color gamut (NTSC) of 131% [ 37 ].…”
Section: Introductionmentioning
confidence: 99%